Analisis Kinerja guru berdasarkan aspek Kompensasi, Punishment dan Budaya Kerja di SDIT Assalam Islamic School Juenieb Kabupaten Bireuen - Sabri, Samir; Kamaruddin, Kamaruddin (peusangan, 2023)
Teacher performance analysis is an important part of evaluating school quality. Substantially and empirically, many people have studied it. Researchers try to examine the factors inherent in teachers' lives, such as aspects of compensation, punishment and work culture in schools. This is the focus of research in the case study of SDIT teachers at the Assalam Juenieb Islamic School in Bireuen Regency. Data collection uses a questionnaire that has been tested for validity and reliability. Medium multiple regression analysis method. The research results show that partially compensation, punishment and work culture factors have a significant and positiv influence in supporting efforts to strengthen teacher performance. Apart from that, these three aspects simultaneously contributed 28.3% to increasing teacher performance.